(untitled) (Economic and Political Thought, 2016)
The main purpose of the paper is to provide a critical overview and analysis of literature concerning expected and predicted macroeconomic effects of the TTIP on the EU and the US. The paper contains information on the main points that are being negotiated by the representatives of the EU and the US. We also try to shed some light on the social expectations of the TTIP, which we discuss with reference to Eurobarometer and Bertelsmann Foundation survey results. The CGE model results together with the critique and macroeconomic consequences of the TTIP are captured, too. Moreover, these are compared to the experience of NAFTA – the agreement between the USA, Canada and Mexico, which has been in force for 22 years now. A comparative analysis of NAFTA ex ante models and the results of empirical research ex post shows that most ex ante models overestimated benefits and underestimated losses of the Free Trade Agreement. NAFTA experience emphasises weaknesses of ex ante models and shows that a mismatch between real and estimated effects of NAFTA can be an indicative answer to the question about the scale of a mismatch between the TTIP prospective and real influence.